es Osmoconditioning of Zea mays Seeds with Plant Extracts to Increase Vigor in Establishment (2021)
Given the cultural and economic importance for Mexico of maize cultivation, and the effects on germination and initial development caused by weeds, phytopathogens and adverse environmental conditions, the objective of this research was to evaluate the effect of osmoconditioning of maize seeds on germination and initial development. Two tests were carried out; in the first one, the effect of three plant extracts was studied: Cinnamomum zeylanicum, Azadirachta indica and Zingiber officinale; sodium bicarbonate and lean biofertilizer. The first with eleven treatments in a completely randomized design, in which the emergence speed and the germination percentage were quantified. In the second test, nine treatments were studied, which consisted of the concentrations that allowed germination in the first test; as variables, height, weight of total fresh and dry matter, and root volume were quantified. Local seeds from Chiapas were used. Sowing was carried out in a green house in sterile sand. The seeds treated with sodium bicarbonate and C. zeylanicum 10% (V:V) had higher emergence speed; the sodium bicarbonate treatment (30 g/L) favored germination and together with the treatments C. zeylanicum at 10% (V:V) A. indica at 20% (V:V) and Z. officinale at 30% (V:V) registered the highest values of fresh root weight, fresh and dry weight of aerial biomass, also stimulated aerial growth 56% with respect to the control treatment (p <0.05). The plant extracts of C. zeylanicum, A. indica and Z. officinale at low concentrations stimulate root and aerial growth, and inhibit the growth of phytopathogenic fungi on seeds and roots when sowing, while at concentrations of 100% they inhibit the germination of  Z. mayz seeds.